Development of Shear Stress Equation Contributing from Steel Fibre in Reinforced Concrete - Sharifah Maszura, Syed Mohsin; Noor Nabilah, Sarbini; I. S., Ibrahim; A. A., Saim (2015)
The raised of extensive research and development on the application of steel fibre inside concrete is a tremendouse topic in a last few decades. The discreet steel fibre have an ability to restrained early cracking formation and next delay the cracking propagation at later stage, when inside concrete. The most obvious benefits of adding steel fibre inside concrete can be seen for the improvement of the mechanical properties of steel fibre reinforced concrete (SFRC). The improvement on the mechanical properties can be seen easily on the higher value of strengths for SFRC compared to plain concrete. However, a question arise on to what extend the steel fibre supplied an additional stress to increased the strength. Currently, this additional stress is called as a shear supplement. In this study, shear supplement model developed by RILEM is quantified with some statistical modification to predicts the additional shear supplied by steel fibre when inside concrete. The modified equation was then used to predicts the value of the shear supplement. Results shows that, the modified model predicts the shear supplement by steel fibres well, shown by higher coefficient of correlation.